Administrando a ferramenta Kanban no comércio - RAMOS, Anderson; RIBEIRO, Daiana; SOUSA, Eduardo; SOUSA, Hugo Luis Teixeira de; OLIVEIRA, Karine; RAMOS, Kelly; PINHEIRO, Maria de Fátima Lenir; ALVES, Priscila; APARECIDO, Rafael; WESLEY, Welisson (166, 2011)
-
Keywords: Softwares; Comércio; Gestão e Negócios